A practical investigation on nickel plated copper heat spreader with different catalytic activation processes for flip-chip ball grid array packages - Amin N.; Lim V.; Seng F.C.; Razid R.; Ahmad I. (2023)
This study investigates the effects of two different catalytic activation techniques on the thermal performance of the flip-chip heat spreaders. The two activation techniques studied are thin nickel-copper strike and galvanic initiation. Thermal diffusivity and surface roughness of these heat spreaders were studied using the Nano-flash Apparatus and Infinite Focus Microscopy. High temperature storage tests were carried out to investigate the extent of intermetallic diffusion between the nickel and copper layers. The results show that heat spreaders with thin nickel-copper strike catalytic activation technique have a lower thermal diffusivity due to the low thermal conductivity of nickel-copper layer. Moreover, the nickel-copper layers grew thicker from around 0.2 ?m at initial time to around 0.55 ?m after high temperature storage duration of 168 h. On the other hand, heat spreaders processed using the galvanic initiation technique did not form any nickel-copper intermetallic diffusion layer. As a conclusion, the galvanic initiation technique can potentially provide better thermal performance for heat spreaders used in semiconductor packages. 2009 Elsevier Ltd. All rights reserved.